2014
DOI: 10.1158/0008-5472.can-14-1420
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide Protein Kinase PDPK1 Is a Crucial Cell Signaling Mediator in Multiple Myeloma

Abstract: Multiple myeloma is a cytogenetically/molecularly heterogeneous hematologic malignancy that remains mostly incurable, and the identification of a universal and relevant therapeutic target molecule is essential for the further development of therapeutic strategy. Herein, we identified that 3-phosphoinositide-dependent protein kinase 1 (PDPK1), a serine threonine kinase, is expressed and active in all eleven multiple myeloma-derived cell lines examined regardless of the type of cytogenetic abnormality, the mutat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Importantly, this pathway is upregulated by Akt inhibition, and dual inhibition of both pathways using Akt inhibitors and MEK inhibitors shows synergistic anti-tumor effects [70, 72, 83]. More recently, 3-phosphoinositide–dependent protein kinase 1 (PDPK1) inhibitor has been shown to induce growth inhibition and apoptosis in MM cells through blockade of both RSK2, a mediator of MAPK/ERK pathway, and Akt [84], further indicating potential clinical utility.…”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…Importantly, this pathway is upregulated by Akt inhibition, and dual inhibition of both pathways using Akt inhibitors and MEK inhibitors shows synergistic anti-tumor effects [70, 72, 83]. More recently, 3-phosphoinositide–dependent protein kinase 1 (PDPK1) inhibitor has been shown to induce growth inhibition and apoptosis in MM cells through blockade of both RSK2, a mediator of MAPK/ERK pathway, and Akt [84], further indicating potential clinical utility.…”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…Recently, several lines of evidence indicate that PDK1 can be considered as a promising target for anticancer drugs and various classes of small molecular inhibitor targeting PDK1 have been proposed [3234]. In MM, PDK1 is generally active and higher expression than other hematopoietic lineages [17, 35, 36]. Activation of PDK1 is essential for myelomagenesis by regulating RSK2, AKT, c-MYC, IRF4 or cyclin Ds, which accelerates the drug resistance and the disease progression [17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been recently shown that GSK2334470 (GSK-470), a novel and highly specific inhibitor of PDK1 [13], inhibits growth, induces cell cycle arrest and overcomes drug resistance in human cancer cells [1416]. In MM, it was demonstrated that PDK1 is expressed and active in all eleven MM-derived cell lines, regardless of the type of cytogenetic abnormality or the status of upstream signaling molecules, and that genetic or pharmacological (BX-912) inhibition of PDK1 caused the growth inhibition and the induction of apoptosis, and augmented the in vitro cytotoxic effects of antimyeloma agents such as melphalan, etoposide, or bortezomib [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In some embodiments, the therapeutic inhibitor (i.e., X-chromosome reactivator) is a selective mTOR inhibitor such as rapamycin, KU-0063794 or everolimus. Many of these targets are downstream substrates of PDPK1, a phosphoinositide protein kinase that regulates PI3K/AKT signaling, and is involved in cancer progression [22]. Extensive biological data show that all these combinations reactivate expression of MECP2 in vitro and in mouse models.…”
Section: Wo/2016/164295mentioning
confidence: 99%